The Complete Chloroplast Genome of Tornillo (Cedrelinga cateniformis Ducke 1922, Fabaceae) - Nora Scarcelli; Cédric Mariac; Marie Couderc; Diana Castro Ruiz; Guillain Estivals; Carlos Alberto Custodio Angulo Chavez; Hector Acho Vasquez; Jhon Gregory Alvarado Reategui; Tony Vizcarra Bentos; Carmen Garcia‐Davila (Ecology and Evolution, 2025)
ABSTRACT Tornillo (Cedrelinga cateniformis Ducke 1922) is a tropical tree of the Fabaceae family. It is commonly used in the lumber factory and is an interesting substitute to overexploited tropical timber species. We sequenced and assembled the first whole chloroplast genome of Tornillo, using Oxford Nanopore technology. The Tornillo's chloroplast is a circular molecule of 176,700 bp with 138 genes and a classic quadripartite structure. The Inverted Repeats present a huge expansion, combined to a strong reduction of the Short Single Copy. Similar results were previously observed in other species of the tribe Ingeae. A maximum likelihood phylogenetic tree reveals a clear distinction of the Ingeae tribe from other tribes (Acacieae and Mimoseae) of the Fabaceae family.